2021
DOI: 10.1002/ags3.12532
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Changes Assessed by Preoperative Computed Tomography Images Can Predict the Long‐Term Prognosis of Stage III Colorectal Cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Results our present study show that patients in the lower SMR group suffered from lower continuation and a higher treatment stop rate due to the adverse effects associated with the postoperative CAPOX therapy. In our previous study, SMI in men and SMR in women were prognostic factors for Stage III colorectal cancer [11]. Based on these previous results, although we anticipated that SMI would also be a risk factor for the discontinuation of adjuvant chemotherapy, our present results did not show this (data not shown).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Results our present study show that patients in the lower SMR group suffered from lower continuation and a higher treatment stop rate due to the adverse effects associated with the postoperative CAPOX therapy. In our previous study, SMI in men and SMR in women were prognostic factors for Stage III colorectal cancer [11]. Based on these previous results, although we anticipated that SMI would also be a risk factor for the discontinuation of adjuvant chemotherapy, our present results did not show this (data not shown).…”
Section: Discussioncontrasting
confidence: 53%
“…Myopenia and myosteatosis could also be a prognostic factor in colorectal cancer (CRC) [1-4, 6, 8-10]. We previously demonstrated that skeletal muscle changes were a predictor of long-term prognosis in Stage III CRC [11]. In this previous study, low skeletal muscle index (SMI), which re ects myopenia, was the prognostic factor in men, while low skeletal muscle radiodensity (SMR) was the predictor in women.…”
Section: Introductionmentioning
confidence: 99%
“…Each tissue type at the L3 level was evaluated in every CT image and marked with different colors (Figure 1). Sarcopenia was assessed through the skeletal muscle index (SMI), calculated as [SMA/height squared (m²)], while myosteatosis was assessed by the average SMA degeneration (17). The myosteatosis thresholds were set at 41 HU for patients with a body mass index (BMI) < 25 kg/m² and 33 HU for patients with a BMI ≥ 25 kg/m² (18).…”
Section: Body Composition Analysis Based On Ctmentioning
confidence: 99%